Nonviolent activism in Islam the message of Abul Kalam Azad - Alvi, Hayat (Lexington Books, 2021)
"The purpose and focus of this study are to illustrate the legal basis for nonviolent activism in Islam, as Maulana Abul Kalam Azad promoted. Maulana Azad's practice of nonviolent activism as a means to expel British colonialism from India provides a potent counterargument against Islamist extremism"--